Probing dynamic self-reconstruction on perovskite fluorides toward ultrafast oxygen evolution - Zhang, Jing (2023)
Exploring low cost, highly active, and durable electrocatalysts for oxygen evolution reaction (OER) is of prime importance to boost energy conversion efficiency. Perovskite fluorides are emerging as alternative electrocatalysts for OER, however, their intrinsically active sites during real operation are still elusive. Herein, the self-reconstruction on newly designed NiFe coupled perovskite fluorides during OER process is demonstrated. In situ Raman spectroscopy, ex situ X-ray absorption spectroscopy, and theoretical calculation reveal that Fe incorporation can significantly activate the self-reconstruction of perovskite fluorides and efficiently lower the energy barrier of OER. Benefiting from self-reconstruction and low energy barrier, the KNi0.8 Fe0.2 F3 @nickel foam (KNFF2@NF) electrocatalyst delivers an ultralow overpotential of 258 mV to afford 100 mA cm-2 and an excellent durability for 100 h, favorably rivaling most the state-of-the-art OER electrocatalysts. This protocol provides the fundamental understanding on OER mechanism associated with surface reconstruction for perovskite fluorides.